Ghosthunters and the Incredibly Revolting Ghost / 1. - Funke, Cornelia (Ghosthunters, 2006)
A timid boy named Tom reluctantly agrees to help professional ghostbuster Hetty Hyssop dispel an IRG (Incredibly Revolting Ghost) from an old house.